Compromised Protein Prenylation as Pathogenic Mechanism in Mevalonate Kinase Deficiency - Politiek, Frouwkje A.; Waterham, Hans R. (Frontiers in Immunology, 2021)
The autoinflammatory and metabolic disorder mevalonate kinase deficiency (MKD) is characterized by life-long recurring episodes of fever and inflammation often without clear cause. MKD is caused by bi-allelic pathogenic variants in the MVK gene, resulting in decreased activity of the encoded enzyme mevalonate kinase (MK). MK is an essential enzyme in the isoprenoid biosynthesis pathway, which generates both non-sterol and sterol isoprenoids. The inflammatory symptoms of patients with MKD point to a major role for isoprenoids in the regulation of the innate immune system. In particular a temporary shortage of the non-sterol isoprenoid geranylgeranyl pyrophosphate (GGPP) is increasingly linked with the inflammation in MKD. The shortage of GGPP compromises protein prenylation, which is thought to be one of the main causes leading to the inflammatory episodes in MKD. In this review we discuss current views and the state of knowledge on the pathogenetic mechanisms in MKD with particular focus on the role of compromised protein prenylation.